Transparency and Accountability in the Management Of Zakat at the Badan Amil Zakat Nasional (BAZNAS) in Kediri City - Porwati , Sinta (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2024)
This study aims to evaluate the level of transparency and accountability in zakat management at the National Amil Zakat Agency (BAZNAS) in Kediri City. The respondents in this study were 65 muzakki. This research used a quantitative method with a questionnaire as the instrument, which was tested for validity and reliability using the SPSS application. The results of the study indicate that the transparency and accountability in zakat management at BAZNAS Kediri City are in the good category. The validity and reliability tests show that the instruments used in this study are valid, ensuring that the results are scientifically accountable. These findings suggest that BAZNAS Kediri City has successfully fulfilled its role in maintaining muzakki trust through the applied transparency and accountability practices. Therefore, this research is expected to serve as a reference for other zakat management institutions to continually enhance their standards of transparency and accountability in zakat management.